Comparison of surface roughness and hardness of three different brands of esthetic coated NiTi archwires: invitro study - Amira A. Aboalnaga; Amal M. El Shahawi (BMC, 2023)
Abstract Background The purpose of the current in vitro study was to evaluate the surface roughness and hardness of three brands of as-received esthetic coated NiTi archwires and compare them with the same parameters after immersion in artificial saliva. Methods Three groups of 0.016 × 0.022 inch epoxy-coated NiTi orthodontic wires [Tooth tone coated NiTi (Ortho Technology, West Columbia, USA), EverWhite NiTi (American Orthodontics, Wisconsin, USA) and Nitanium Super Elastic Tooth Tone Plastic coated (Ortho Organizers, San Marcos, CA, USA)] were compared. Each group was subdivided into five as-received archwire specimens and five archwire specimens retrieved following immersion in artificial saliva for 28 days. Atomic force microscopy was used for analysis of average surface roughness (Sa). Hardness testing was performed using Digital Vickers hardness tester. ANOVA and Kruskal-Wallis tests were used for comparing the wire groups. Results The ranking of (Sa) values was as follows: Nitanium Ortho Organizers > Everwhite American Orthodontics > Tooth tone Ortho Technology (P > 0.05). Nitanium Ortho Organizers archwires showed significantly greater (Sa) than both other groups following immersion in saliva (P < 0.001). The coating hardness of as-received and post-immersion archwires from Tooth tone Ortho Technology was significantly lower than the other groups (P < 0.001). For all the three types of archwires, the mean hardness of immersed wires was significantly lower than that of the as-received archwires (P < 0.001). Conclusions Esthetic coated archwires have shown unpleasant surface changes following exposure to artificial saliva. These surface changes are affected by physical characteristics such as surface roughness and hardness of the coating.